Antiviral molecules correlate with vitamin D pathway genes and are associated with natural resistance to HIV-1 infection (2016)
The relationship between the immunomodulatory effects of Vitamin D (VitD) and the expression of anti-HIV-1 molecules has not been explored in HIV-1-exposed seronegative individuals (HESNs). Higher mRNA levels of cathelicidin and HAD-4 in oral-mucosa and peripheralblood, along with higher CYP24A1 mRNA in vaginal-mucosa and lower TLR2 mRNA in endocervical-mucosa were found in HESNs compared to non-exposed controls. Furthermore, the mRNA of anti-HIV molecules Elafin, TRIM5, Cathelicidin, HAD-4 and RNase7, previously associated with natural resistance to HIV-1 infection, positively correlated with the mRNA expression of VDR in HESNs, suggesting the potential participation of VitD in natural resistance to HIV-1.